Efficacy of vitamin D3 supplementation in reducing incidence of pulmonary tuberculosis and mortality among HIV-infected Tanzanian adults initiating antiretroviral therapy: study protocol for a randomized controlled trial. Issue 1 (December 2017) - Sudfeld, Christopher; Mugusi, Ferdinand; Aboud, Said; Nagu, Tumaini; Wang, Molin; Fawzi, Wafaie
Abstract Background HIV-infected adults initiating antiretroviral therapy (ART) in sub-Saharan Africa continue to experience high rates of morbidity and mortality during the initial months of treatment. Observational studies in high-income and resource-limited settings indicate that HIV-infected adults with low vitamin D levels may be at increased risk of mortality, HIV disease progression, and incidence of pulmonary tuberculosis (TB). As a result, vitamin D3 supplementation may improve survival and treatment outcomes for HIV-infected adults initiating ART. Methods/Design The Trial of Vitamins-4 (ToV4) is an individually randomized, double-blind, placebo-controlled trial of vitamin D3 (cholecalciferol) supplementation conducted among 4000 HIV-infected adults with low vitamin D levels [25-hydroxyvitamin D (25(OH)D) <30 ng/mL] initiating ART in Dar es Salaam, Tanzania. The two primary aims of the trial are to determine the effect of a vitamin D3 supplementation regimen on incidence of (1) mortality and (2) pulmonary TB as compared to a matching placebo regimen. The primary safety outcome of the study is incident hypercalcemia. The investigational vitamin D3 regimen consists of oral supplements containing 50, 000 IU vitamin D3 taken under direct observation at randomization and once a week for 3 weeks (four doses) followed by daily oral supplements containing 2000 IU vitamin D3 taken at home from the fourth week until trial discharge at 1 year post ART initiation. Trial participants are followed up at weekly clinic visits during the first month of ART and at monthly clinic visits thereafter until trial discharge at 1 year post ART initiation. Secondary aims of the trial are to examine the effect of the vitamin D3 regimen on CD4 T cell reconstitution, incidence of non-TB comorbidities, body mass index (BMI), depression and anxiety, physical activity, bone health, and immunologic biomarkers. Discussion The ToV4 will provide causal evidence on the effect of vitamin D3 supplementation on incidence of pulmonary TB and mortality among HIV-infected Tanzanian adults initiating ART. The trial will also give insight to whether vitamin D3 supplementation trials for the prevention of pulmonary TB should be pursued in HIV-uninfected populations. Trial registration ClinicalTrials.gov, NCT01798680 . Registered on 21 February 2013.